2005
DOI: 10.1021/bi050792f
|View full text |Cite
|
Sign up to set email alerts
|

Identification in the Mold Hypocrea jecorina of the First Fungal d-Galacturonic Acid Reductase

Abstract: A d-galacturonic acid reductase and the corresponding gene were identified from the mold Hypocrea jecorina (Trichoderma reesei). We hypothesize that the enzyme is part of a fungal d-galacturonic acid catabolic pathway which has not been described previously and which is distinctly different from the bacterial pathway. H. jecorina grown on d-galacturonic acid exhibits an NADPH-dependent d-galacturonic acid reductase activity. This activity is absent when the mold is grown on other carbon sources. The d-galactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…Although a large number of yeasts and molds can use galacturonic acid as a carbon and energy source for growth, knowledge of the metabolic route for D-galacturonic acid catabolism in eukaryotes is surprisingly limited (Kuorelahti et al 2005;Visser et al 1988). It has been concluded that D-galacturonic acid is metabolized through glyceraldehyde and pyruvate (Visser et al 1988).…”
Section: Galacturonic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a large number of yeasts and molds can use galacturonic acid as a carbon and energy source for growth, knowledge of the metabolic route for D-galacturonic acid catabolism in eukaryotes is surprisingly limited (Kuorelahti et al 2005;Visser et al 1988). It has been concluded that D-galacturonic acid is metabolized through glyceraldehyde and pyruvate (Visser et al 1988).…”
Section: Galacturonic Acidmentioning
confidence: 99%
“…It has been concluded that D-galacturonic acid is metabolized through glyceraldehyde and pyruvate (Visser et al 1988). Kuorelahti et al (2005) have recently identified a D-galacturonic acid reductase in the mold Hypocrea jecorina. This enzyme converts D-galacturonic acid and NADPH to L-galactonic acid and NADP + .…”
Section: Galacturonic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two steps of this pathway have been described. In the first step D-galacturonate is reduced to L-galactonate by an NADPH-coupled D-galacturonate reductase (6). In Hypocrea jecorina (Trichoderma reesei) this enzyme activity was induced when grown on D-galacturonate but the activity was absent during growth on other carbon sources.…”
mentioning
confidence: 99%
“…In Hypocrea jecorina (Trichoderma reesei) this enzyme activity was induced when grown on D-galacturonate but the activity was absent during growth on other carbon sources. The D-galacturonate reductase gene gar1 is identified and the purified protein characterized (6). In the second step L-galactonate is converted to L-threo-3-deoxy-hexulosonate (2-keto-3-deoxy-L-galactonate) by a dehydratase (7).…”
mentioning
confidence: 99%